The effects of general anaesthesia on oxygen consumption: A meta‐analysis guiding future studies on perioperative oxygen transport. Issue 2 (20th September 2018) - Jakobsson, Julia; Vadman, Sofia; Hagel, Eva; Kalman, Sigridur; Bartha, Erzsébet
Abstract : Background: Increased oxygen extraction, the ratio of consumption to delivery, has been associated with poor outcome after surgery. Oxygen consumption (VO2) can change in several ways in the perioperative period, but is seldom monitored directly in routine care. This study investigates the effects of general anaesthesia on VO2. Methods: We searched PubMed, EMBASE, and Cochrane Library 1946‐2018 for studies including VO2 measurements before and after anaesthesia induction. Quality was assessed by Cochrane risk of bias tool and NIH Quality Assessment tool for before‐and‐after studies. Changes in VO2 after anaesthesia induction were pooled in a random effects model meta‐analysis with standardized mean differences transformed to absolute changes of VO2. Changes in VO2 after surgical incision and after recovery from anaesthesia were analysed as secondary outcomes in the included studies. Results: Twenty‐four studies including 453 patients were analysed for VO2 changes induced by anaesthesia. Studies were published during 1969‐2000 and mean age of patients ranged 28‐70 years. VO2 decreased after anaesthesia induction by −65 (−75; −55, 95% CI) mL min −1 and indexed VO2 (VO2I) by −33 (−38; −28, 95% CI) mL min −1  m −2 . After surgical incision and in the post‐operative period VO2 increased again. Heterogeneity was considerable among the studies and the overall quality of evidence was very low. Conclusions: General anaesthesia probably reduces oxygen consumption but the effect estimate is uncertain. Given the limited generalizability and low quality of the available evidence, new studies in modern perioperative settings and in today's older high‐risk surgical patient populations are needed.